Norman Mailer [videorecording] - Mailer, Norman; Weyhmuller, Hans-Jorge (Profile of a writer, 1987)
Presents interviews with Mailer & family and clips from his films. The author talks about his generation, drugs and power, sports and others. Mailer discusses also his views of immortality in the light of his book about the murderer Gary Gilmore, The Executioner's Song.